An Unusual Presentation of Pseudothrombotic Microangiopathy in a Patient with Autoimmune Atrophic Gastritis - Alexandre Malek; Roy Nasnas (Case Reports in Hematology)
Introduction. We hereby describe the case of a young female patient who presented with pseudothrombotic microangiopathy, as well as pancytopenia accompanied by autoimmune atrophic gastritis. Case Presentation. A 36-year-old Caucasian woman presented to the emergency department with fatigue and dyspnea on minimal exertion. Physical examination was unremarkable except for pallor and noninjected conjunctiva. Laboratory tests revealed high LDH and low hemoglobin, white blood cells, platelets, and haptoglobin. The peripheral blood smear showed schistocytes suggestive of pseudothrombotic microangiopathy. Low cobalamin level and hyperhomocysteinemia were also detected. Autoimmune atrophic gastritis was confirmed by gastric biopsy and positive anti-intrinsic factor antibodies. Vitamin B12 supplements were given which led to rapid recovery and normalization of blood parameters. Conclusion. This case highlights the importance and serves as a reminder to clinicians to rule out cobalamin deficiency and autoimmune atrophic gastritis in patients presenting with a picture suggestive of thrombotic thrombocytopenic purpura and pancytopenia, which was completely reversible after appropriate replacement therapy without recurring to unnecessary and invasive procedures such as plasma exchange.